Analysis of Interactive Multimedia UI/UX Structure in Dynamic Game Play as Learning Media in Solar System Physics Laboratory - Karisma, Bisma; Cahyadi , Arif Tri (Journal of Multimedia Trend and Technology, 2025)
Multimedia can collaborate between text, sound, photos, animation, and video elements through digitally manipulated computer devices by conveying information, and controlled interactively. Interactive multimedia in this learning can be a problem solver in learning in the digital era to trigger intelligence in students' thinking. Not all games have a basis in learning that is in accordance with its dimensions, namely cognitive and psychomotor. The information presented may not be processed properly by the brain, not stored in long-term memory, or cannot be applied in other contexts. Games that are not designed with consideration of how players build understanding can lead to misconceptions or shallow understanding of the material being taught. If the game is not cognitively challenging or does not stimulate critical thinking, players may feel bored or uninterested. This will reduce their motivation to continue playing and learning. The purpose of this study is to test the theory of interactive multimedia elements used in Interactive Media in learning in the Solar System Physics laboratory as a supplement to electronic learning. This research method was carried out using a descriptive qualitative approach regarding the results of the study of the interactive multimedia design structure in the Dynamic Game of the Solar System Physics Lab. The results of this study provide an overview of the interactive multimedia design structure that can be used as a reference for teachers and interactive multimedia developers.